Robotic DIEP Patient Selection: Analysis of CT Angiography. Issue 12 (7th December 2021) - Kurlander, David E.; Le-Petross, Huong T.; Shuck, John W.; Butler, Charles E.; Selber, Jesse C.
Abstract : Background: Preoperative CTA is widely used and extensively studied for planning of DIEP flap breast reconstruction. However, its utility in planning robotic DIEP harvest is undescribed. Methods: The authors conducted a retrospective study of consecutive patients presenting to the clinics of select plastic surgeons between 2017 and 2021 for abdominally based autologous breast reconstruction. CTA measurements of intramuscular perforator distance and perforator-to-external iliac distance were used as predicted robotic and open fascial incision lengths, respectively. It was documented if the predicted robotic incision would avoid crossing the arcuate line. Operative notes were reviewed for fascial incision length and number of perforators harvested. Predicted and actual robotic fascial incision lengths were compared. Results: CTAs were reviewed for 49 patients (98 hemiabdomens). Inadequate or no perforators were identified on CTA in 18% of hemiabdomens. Mean predicted robotic and open DIEP fascial incisions were 3.1 cm and 12.2 cm, respectively, giving robotic approach fascial incision benefit of 9.1 cm ( P < 0.001). The predicted robotic incision avoided crossing the arcuate line in 71% of hemiabdomens. Thirteen patients (28%) underwent robotic DIEP harvest. Actual robotic fascial incision length averaged 3.5 cm, which was not significantly different from the mean predicted fascial incision length ( P = 0.374). Robotic DIEP flaps had fewer perforators (1.8 versus 2.6, P = 0.058). Conclusion: CTA is useful for identifying patients with anatomy favorable for robotic DIEP flap harvest.